Pharmacological inhibition of LSD1 for the treatment of MLL-rearranged leukemia - Zizhen Feng; Yuan Yao; Chao Zhou; Fengju Chen; Fangrui Wu; Liping Wei; Wei Liu; Shuo Dong; Michele Redell; Qianxing Mo; Yongcheng Song (Journal of Hematology & Oncology, 2016)
Abstract Background Mixed lineage leukemia (MLL) gene translocations are found in ~75 % infant and 10 % adult acute leukemia, showing a poor prognosis. Lysine-specific demethylase 1 (LSD1) has recently been implicated to be a drug target for this subtype of leukemia. More studies using potent LSD1 inhibitors against MLL-rearranged leukemia are needed. Methods LSD1 inhibitors were examined for their biochemical and biological activities against LSD1 and MLL-rearranged leukemia as well as other cancer cells. Results Potent LSD1 inhibitors with biochemical IC50 values of 9.8–77 nM were found to strongly inhibit proliferation of MLL-rearranged leukemia cells with EC50 of 10–320 nM, while these compounds are generally non-cytotoxic to several other tumor cells. LSD1 inhibition increased histone H3 lysine 4 (H3K4) methylation, downregulated expression of several leukemia-relevant genes, induced apoptosis and differentiation, and inhibited self-renewal of stem-like leukemia cells. Moreover, LSD1 inhibitors worked synergistically with inhibition of DOT1L, a histone H3 lysine 79 (H3K79) methyltransferase, against MLL-rearranged leukemia. The most potent LSD1 inhibitor showed significant in vivo activity in a systemic mouse model of MLL-rearranged leukemia without overt toxicities. Mechanistically, LSD1 inhibitors caused significant upregulation of several pathways that promote hematopoietic differentiation and apoptosis. Conclusions LSD1 is a drug target for MLL-rearranged leukemia, and LSD1 inhibitors are potential therapeutics for the malignancy.